Sediment production modelling in a basin with little information including the potential effects of climate change and land use change - Orozco Medina, Ismael; Ramos Castillo, Luis Alberto (Acta Universitaria, 2020)
The potential effects of climate change and land use change make it essential to assess the processes of erosion and sediment transport in current and future situations. However, evaluating these processes correctly is not easy, because there is no information for the calibration and validation of mathematical models. This research proposes a methodological alternative for the calibration of a sedimentological model in basins without information and for modeling these processes, including the effects of climate change and land use change. The results foresee an increase in runoff (up to 1 m3s-1) in the future as well as reductions in the transport of sediments (0.0003 m3s-1) and erosion (5%), compared to the current one in the Turbio river sub-basin.